COMPUTATIONAL THINKING SEBAGAI STRATEGI PEMBELAJARAN OPERASI HITUNG UNTUK MENGEMBANGKAN LITERASI NUMERASI KELAS 5 - Novia Mahera Shafitri; Eka Sastrawati; Violita Zahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Numeracy literacy is one of the essential competencies that elementary school students must master to solve mathematical problems in daily life. However, arithmetic learning in elementary schools is often still procedural and less oriented toward developing higher-order thinking skills. This study aims to examine computational thinking as a learning strategy in arithmetic operations to develop numeracy literacy of fifth-grade students. The research employed a quantitative approach using a one-group pretest–posttest design involving 20 fifth-grade students. Data were collected through numeracy literacy tests administered before and after the implementation of computational thinking-based instruction. The data were analyzed using descriptive statistics and paired sample t-test. The results indicate a significant improvement in students’ numeracy literacy after participating in arithmetic learning based on computational thinking. These findings suggest that computational thinking is an effective strategy for enhancing numeracy literacy in elementary school arithmetic learning.